Transformer une équation quotient pour la résoudre Exercice

Quelle est la solution de l'équation suivante ?

\(\displaystyle{\dfrac{x-4}{x-1}=-\dfrac{4}{x}}\)

Quelle est la solution de l'équation suivante ?

\(\displaystyle{\dfrac{3}{x}-\dfrac{2}{x+2}=\dfrac{4}{x\left(x+2\right)}}\)

Quelle est la solution de l'équation suivante ?

\(\displaystyle{\dfrac{x}{x-1}=\dfrac{x-2}{x}}\)

Quelle est la solution de l'équation suivante ?

\(\displaystyle{\dfrac{2x-8}{x-2}=4}\)

Quelle est la solution de l'équation suivante ?

\(\displaystyle{\dfrac{x^{2}}{x+1}=3+x}\)

Quelle est la solution de l'équation suivante ?

\(\displaystyle{\dfrac{4}{x+3}=\dfrac{2}{x+1}}\)

Quelle est la solution de l'équation suivante ?

\(\displaystyle{\dfrac{2x-3}{2x-1}=\dfrac{2x+4}{2+2x}}\)

Suivant